2014
DOI: 10.1590/1413-78522014220600451
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Q angle in differents static postures

Abstract: OBJECTIVE: To compare the value of Q angle in different positions, in the external and internal rotations of lower limbs. METHODS: This is a descriptive cross-sectional study. We have evaluated 62 volunteers, 32 women and 30 men in the following positions: supine positions with parallel feet, supine with abduction (external rotation of lower limbs), and standing position with parallel feet and with external rotation. All the participants were sedentary and without previous history of acute injury or complaints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 19 publications
1
25
0
3
Order By: Relevance
“…However, when comparing the Q angle in the supine posture no statistical differences were found i.e. the values of the Q angle did not change with the limb rotation in this position, suggesting that because of the absence of muscle contraction promoting muscle relaxation and release of the patellofemoral joint [4]. It was found that there could be within subject and between gender asymmetry in Q angle.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, when comparing the Q angle in the supine posture no statistical differences were found i.e. the values of the Q angle did not change with the limb rotation in this position, suggesting that because of the absence of muscle contraction promoting muscle relaxation and release of the patellofemoral joint [4]. It was found that there could be within subject and between gender asymmetry in Q angle.…”
Section: Introductionmentioning
confidence: 78%
“…This was measured using a universal goniometer. The participant was then asked to lie down in supine position with neutral joint alignment [4]. Again the anatomical landmarks as above were marked and Q angle was measured.…”
Section: Study Proceduresmentioning
confidence: 99%
“…Traditionally measured with the patient supine and quadriceps relaxed, there has not yet been a standardization of the position and state of muscle contraction while measuring the Q angle. 22,23 It is an indicator of the net lateral force exerted on the patella by the quadriceps and the patellar tendon. 24 Q angle of more than 14° in males and more than 17° in females suggests abnormal lateralization of the tibial tubercle.…”
Section: Trochlear Depth >3-5 MMmentioning
confidence: 99%
“…In many studies, it has been emphasized that measurement position caused a change in Q angle ( 19 , 36 ). When we compared the mean Q angle values measured in the supine and standing positions in our study in this context, no significant difference was found.…”
Section: Discussionmentioning
confidence: 99%
“…We think that lack of a difference between measurement positions was associated with compensation of increased pelvic width by way of lateral movement of the patella, as stated by Guerra et al ( 8 ). Another factor is the fact that standardization of the measurement position has not yet been provided ( 19 , 25 , 36 ). In the literature, the Q angle has been measured in the supine position with the knee in 20–25° flexion in some studies, and it has been measured with the knee in extension in some other studies, similar to our study ( 25 , 27 , 30 ).…”
Section: Discussionmentioning
confidence: 99%